Teachers’ Perceptions and Practices of Reward and Punishment in Islamic Religious Education - Dini Permana Sari; Yani Mulyani Rahayu (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: The main objective of this study is to describe how teachers of Islamic Religious Education perceive the concepts of reward and punishment, how they understand their educational functions, and how they implement these strategies effectively in Islamic Religious Education learning processes at vocational high schools that are integrated with Islamic boarding schools and their moral values. Methodology: This research employed a qualitative descriptive approach using a field study design. Data were collected through in-depth interviews with teachers and key informants, classroom observations, and document analysis. The analytical framework was based on Skinner’s operant conditioning theory, including positive and negative reinforcement and punishment types I and II, to interpret teachers’ perceptions and educational practices within Islamic learning contexts. Main Findings: The findings indicate that teachers of Islamic Religious Education generally hold positive perceptions of reward and punishment in the learning process. Reward is considered an effective positive reinforcement to enhance students’ motivation, participation, and discipline, while punishment is implemented as an educational, proportional measure aligned with school regulations and Islamic boarding school culture. Novelty/Originality of this study: This study offers novelty by examining teachers’ perceptions and the implementation of reward and punishment within Islamic Religious Education learning at vocational high schools integrated with Islamic boarding schools, using an operant conditioning framework. The findings contribute to Islamic educational psychology by emphasizing humanistic and contextually grounded reinforcement and punishment practices that foster moral development, character building, and value-based learning